Evaluasi Penerapan PPh Pasal 23 Atas Jasa Konstruksi Pada CV. Lambatorang Abadi Jaya - Resky Amelia; Imron Burhan; Mahardian Hersanti Paramita (Politeknik Bosowa, 2021)
Construction services have a major role in activities in the economic, social and cultural fields in the achievement of various supporting facilities for national development. With a very important role and quite a different nature, the government regulates itself regarding the treatment of PPh on this construction service. This research was conducted at CV. Lambatorang Abadi Jaya, which is a construction service provider, with the aim of knowing the deduction, deposit and reporting of PPh article 23 on construction services between CV. Lambatorang Abadi Jaya with tax regulations related to the application of PPh article 23 on construction services. Data collection techniques using interview and documentation techniques. Data analysis techniques using comparative data analysis techniques. In this study, the authors also conducted interviews at the Maros Primary Tax Office (KPP) to get further explanation regarding the application of PPh article 23 on construction services. The results of this study indicate that, the cuts made by CV. Lambatorang Abadi Jaya is in accordance with applicable regulations, for deposits made by CV. LambatorangAbadi Jaya is still said to be not on time according to the stipulated regulations, and for the reporting itself, it is done correctly and on time in accordance with the applicable regulations.Keyword :Income tax 23, constructions service